Upaya Peningkatan Kompetensi Guru Pendidikan Agama Islam di SMP Swasta Nurulhadina - Khoiron, Fitra; Nasution, Abdul Fattah; P, Juli Julaiha (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to improve the quality of Islamic Religious Education (PAI) teachers at Nurul Hadina Private Middle School through various professional development strategies. This improvement is considered important considering the role of PAI teachers in shaping the character and moral values of students must have maximum competence in educating students. The research method used is the research method. Data were collected through observation, interviews, and documentation. The results of the study showed that the condition of PAI teachers at Nurul Hadina Private Middle School was quite good, with various efforts made by the school, such as implementing evaluations, strengthening relationships between teachers and motivating teachers to continue to develop their competence, participating in training activities. The obstacles experienced include time constraints, lack of use of technology, and age. The solution provided is to routinely increase insight by reading books and articles about improving teacher competence, and providing motivation to teachers to always try to improve their competence.